2011
DOI: 10.1111/j.1745-4565.2011.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Scopoletin in Cassava Products as an Inhibitor of Aflatoxin Production

Abstract: The scopoletin level in a cassava variety from Benin, BEN 86052, and the compounds effect on the growth of an Aspergillus flavus isolate from cassava chips were investigated. The influence on the biosynthesis of aflatoxins was also investigated. Scopoletin was quantified using high performance liquid chromatography. An in vitro test was used to evaluate the inhibitory effects of cassava flour extracts and pure scopoletin on growth and biosynthesis. The A. flavus isolate was genetically characterized to be an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This confirmed the previous studies which reported that cassava products are unlikely to be a source of aflatoxin like maize and groundnuts (Muzanila et al, 2000;Gnonlonfin et al, 2012). Gnonlonfin et al (2011) reported that scopoletin, accumulated in cassava chips, has the potential to inhibit aflatoxin production. In addition, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were also analyzed to determine the toxicology of liver.…”
Section: Discussionsupporting
confidence: 81%
“…This confirmed the previous studies which reported that cassava products are unlikely to be a source of aflatoxin like maize and groundnuts (Muzanila et al, 2000;Gnonlonfin et al, 2012). Gnonlonfin et al (2011) reported that scopoletin, accumulated in cassava chips, has the potential to inhibit aflatoxin production. In addition, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were also analyzed to determine the toxicology of liver.…”
Section: Discussionsupporting
confidence: 81%
“…Among 18 different types of aflatoxins produced by A. flavus strains, aflatoxin B1 (AFB1, Figure 1) is the most extremely toxic, mutagenic and carcinogenic type [31,32]. Thus, numerous studies have been conducted to determine the effects of various food additives, preservatives, chemicals and environmental conditions to inhibit growth and aflatoxin production effectively [33][34][35][36][37][38]. …”
Section: Producing Fungal Speciesmentioning
confidence: 99%
“…In the review by Holmes et al 10) , aflatoxin production inhibitors from plant constituents were classified into a variety of groups such as alkaloids (caffeine, piperine, piperlongumine, pipernonaline, and piperoctadecalidine); phenylpropanoids [coumarins and furanocumarins (bergapten, p-coumaric acid, 5,7-dihydroxychromone, khellin, psoralene, visnagin, and xanthotoxin), flavonoids (amentoflavone, 6,6′ ′-bigenkwanin, 7,7′′-dimethoxyagathisflavone, tetradimethoxy-6,6′′-bigenkwanin, cyanidin, cyanidin 3-galactoside, cyanidin 3-glucoside, delphinidin, eriodictyol, glyceollin, kaempferol, luteolin, malvidin, pelargonidin, pelargonidin 3-glucoside, and peonidin), and phenolics (eugenol, ferulic acid, vanillic acid, vanillylacetone, diferuloylputrescine, and p-coumaroylferuloylputrescine)]; hydroxamic acids (4-acetyl-2-benzoxazolinone and 6methoxy-2-benzoxazolinone); terpenoides (camphene, canthaxanthin, α-carotene, β-carotene, β-cryptoxanthin, αionone, β-ionone, limonene, lutein, lycopene, and zeaxanthin); a tannin component (gallic acid); an inositol derivative (phytic acid), peroxidation products of unsaturated fatty acids, alkyl aldehydes (nonyl aldehyde); and signal molecules (ethylene and methyl jasmonate). Holmes et al summarized aflatoxin production inhibitory activities of these inhibitors in detail and pointed out that many Notes: (9), ethylene (10), (2-chloroethyl)phosphonic acid (11), dillapiol (12), apiol (13), spiroether (14), methyl syringate (15), gallic acid (16), methyl gallate (17), methyl 3,4,5-trimethoxybenzoate 18 plant-derived inhibitors have antioxidant activity, but their modes of action for inhibiting aflatoxin production are not clear.…”
mentioning
confidence: 99%
“…Scopoletin (7) 11) and (E)-2-hexenal (8) 12) were recently reported as the key compounds for obtaining resistance of cassava and soybean seed to aflatoxin contamination, respectively. As scopoletin, a phytoalexin of cassava, showed strong aflatoxin production inhibitory activity against A. flavus at the concentration of 2 mM, and content level of scopoletin in cassava was suggested to correlate with resistant level of cassava to aflatoxin contamination.…”
mentioning
confidence: 99%
See 1 more Smart Citation